(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Relational physics, which I founded, views energy as a relationship (pulse) between objects. It painted a simple real picture of energy pulsing through the rotational motion of each object, creating an alternating relationship between the two extremes. Such a way of looking at things could be an appropriate explanation for various physical phenomena, such as the double-slit experiment and the measurement of electrons in hydrogen atoms. In this paper, the discussion is particularly focused on experiments to investigate the position of electrons. From such challenges, results that could affirm the reality of microscopic objects were obtained. The success of the attempt here tells us that determinism will prevail over non-determinism. The history of physics is about to undergo a major shift.